Kualitas Buah Jeruk (Citrus sp) dari Lima Kabupaten di Sumatra Selatan - Mardiah, N.; Haryanti, D.; Agungtio, R.; Alsada, Muhammad S.; Suryani, Carina N.; Harun, M. Umar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Mardiah, N., Haryanti, D., Agungtio, R., Alsada, M.S., Suryani, C.N., Harun, M.U. (2024). Quality of orange (Cirtus sp) fruit from five districts in South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 118–126). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).South Sumatra is known as one of the provinces that cultivates many citrus fruits of good quality, but with different flavors or morphology. This research aims to determine the quality of each orange from five districts in South Sumatra so that it can be improved again. This research uses a method of comparing the average sampling numbers for citrus fruit from five districts in South Sumatra. All sampling oranges were analyzed at the Agricultural Products Technology Laboratory, Sriwijaya University. From the results obtained, it is clear that oranges from Ogan Komering Ilir District have the best quality because they have the largest diameter, have the brightest skin color, and have the lowest pH level among oranges from other districts, while the lowest quality orange fruit comes from OKU district, all observed variables were analyzed statistically and compared with each other. Based on the results of the study, Siamese oranges from OKU have a fruit diameter (123.7mm), mass (149.66g), and volume (6,048ml) that are greater than Siamese oranges from other districts. Siamese orange juice from OKU has a pH (4,304) greater than others, so Siamese oranges from OKU are sweeter. The research results show that orange fruit from five districts in South Sumatra has different qualities, depending on the climate, soil and cultivation methods used.